Perioperative outcome of Laparoscopic Roux-en-Y gastric bypass: A children's hospital experience - Miyano, Go (2013)
BACKGROUND/PURPOSE: To evaluate the perioperative safety of laparoscopic Roux-en-Y gastric bypass (LRYGB) in a freestanding children’s hospital setting. PATIENTS AND METHODS: Perioperative (<90 days) clinical complications of 77 consecutive patients (mean age 16.8 ± 2.1 years: mean BMI 59.4 kg/m(2), 68% female), who underwent LRYGB at Cincinnati Children’s Hospital from 2002 to 2007 were examined, using standardized data collection forms that were created specifically for use in this study. RESULTS: No mortality or conversion to open surgery was observed. Intraoperative complications were uncommon (3%). No anesthetic complications or transfusion requirements were observed. Median hospital stay was 3 days. Twenty-two percent of subjects had a complication from discharge to 30 days, while 13% experienced a complication between 31 and 90 days. The common types of postoperative complications included gastrojejunal anastomotic stricture (17%), leak (7%), dehydration (7%), and small bowel obstruction (SBO; 5%). Reoperation was required in 9 subjects. Operating time significantly decreased as the number of cases performed increased. CONCLUSIONS: LRYGB in this case series of adolescents was associated with a low rate of intraoperative complications, with an increased rate over the ensuing 90 days. These events can be successfully managed, even in super obese adolescents.